Glimpses of creatures in their physical worlds - Vogel, Steven, 1940-2015 (Princeton University Press, 2009)
Glimpses of Creatures in Their Physical Worlds offers an eye-opening look into how the characteristics of the physical world drive the designs of animals and plants. These characteristics impose limits but also create remarkable and subtle opportunities for the functional biology of organisms. In particular, Steven Vogel examines the size and scale, and trade-offs among different physical processes. He pays attention to how the forms and activities of animals and plants reflect the materials available to nature, and he explores the unique constraints and possibilities provided by fluid flow, s.